Researching the Legal Culture of the Bureaucracy: An Introduction to Ethnographic Study of Procedural Criminal Law (Meneliti Budaya Hukum Aparat: Sebuah Pengantar tentang Etnografi dalam Studi Hukum Acara Pidana) - Afandi, Fachrizal (UI Scholars Hub, 2022)
This article presents the development of ethnographic research to understand the culture and performance of criminal justice actors (i.e. police, prosecutors, judges, probation officers). This article begins by outlining the lack of socio-legal research in Indonesian criminal justice research, which results in a scarcity of academic contributions to criminal justice reform. This article then provides an introduction to how the socio-legal approach influences criminal law research and how the ethnographic approach contributes to the study of criminal justice. Before the final section of this article, I discuss the challenges of conducting ethnographic research and suggestions based on my experience as an ethnographer.